Neurodegenerative changes in patients with clinical history of bipolar disorders. Issue 3 (30th March 2015) - Shioya, Ayako; Saito, Yuko; Arima, Kunimasa; Kakuta, Yukio; Yuzuriha, Takefumi; Tanaka, Noriko; Murayama, Shigeo; Tamaoka, Akira
<x xml:space="preserve">Abstract</x> Neurodegeneration in bipolar disorder (BPD) is poorly understood. Therefore, the current study was designed to assess the immunohistochemical changes in neurodegenerative markers in patients with BPD. Eleven consecutive autopsy cases diagnosed with BPD were analyzed. Sections were obtained from archival paraffin blocks of representative areas and stained using conventional methods, as well as immunostained with several antibodies to screen for neurodegenerative diseases. Age‐ and non‐argyrophilic grains (AGs) degeneration matched controls were selected for each case. Clinical information was retrospectively collected from medical charts. All patients were men, and the average age of death was 70 years. Neuropathological diagnoses included dementia with grains (2), argyrophilic grain disease (2), corticobasal degeneration (CBD, 1), Lewy body disease (1), hypoxic encephalopathy (1) and cerebral infarction (1). All cases showed AGs to various degrees. Three patients died in their 50s; one demonstrated dementia with Lewy bodies, while the other two showed abundant AGs in the thalamus and amygdala. Of the three patients who died in their 60s, one showed AGs preferentially in the thalamus and amygdala, while the others demonstrated limbic predominance. The patients who died in/after their 70s demonstrated AGs similar to controls, except for the patient with CBD. Our data provides potentiality that neurodegenerative diseases may be an underlying pathology in certain cases of BPD.